Identifying IFDI and OFDI Productivity Spatial Spillovers: Evidence from China. Issue 5 (8th April 2020) - Huang, Youxing; Yang, Huixin
ABSTRACT: Using an original and unique merged large-scale Chinese dataset over 2002–2007, this article investigates the productivity spatial spillover effects from both inward and outward foreign direct investment (FDI) to private-owned domestic firms based on intra- and inter-regional dimensions. Results show strong evidence that the positive outward FDI (OFDI) spillover effect dominates in inter-region, whereas no significant positive effect exists in intra-region. By contrast, no significant spatial spillover effect is observed from inward FDI (IFDI). In addition, there exists the optimum geographical distance on productivity spatial spillovers as a result of the non-linear impact of the geographical proximity. These results are robust after controlling potential endogeneity and to different specifications.